A beginner's guide to Amazon web services - Dubey, Parul; Raja, Rohit (CRC Press, Taylor & Francis Group, 2024)
Amazon Web Services (AWS) provides on-demand cloud computing platforms and application programming interfaces (APIs) to individuals, companies, and govern- ments, along with distributed computing processing capacity and software tools via AWS server farms.